2019
DOI: 10.1001/jamanetworkopen.2019.11154
|View full text |Cite
|
Sign up to set email alerts
|

Association of Liver-Directed Local Therapy With Overall Survival in Adults With Metastatic Intrahepatic Cholangiocarcinoma

Abstract: Key PointsQuestionIs the addition of liver-directed local therapy to chemotherapy associated with an improvement to overall survival for patients with metastatic intrahepatic cholangiocarcinoma?FindingsThis cohort study, using data from 2201 patients with metastatic intrahepatic cholangiocarcinoma from the National Cancer Database, found statistically significant higher overall survival in patients treated with chemotherapy and liver-directed surgery or irradiation vs patients treated with chemotherapy alone.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Most of the morbidity and mortality among patients with metastatic ICC is due to liver disease and liver failure. Therefore, the selective use of liver-directed therapies, even in the presence of metastatic disease, may improve local disease control, health related quality of life, and potentially overall survival[ 35 ].…”
Section: Management Of Iccmentioning
confidence: 99%
“…Most of the morbidity and mortality among patients with metastatic ICC is due to liver disease and liver failure. Therefore, the selective use of liver-directed therapies, even in the presence of metastatic disease, may improve local disease control, health related quality of life, and potentially overall survival[ 35 ].…”
Section: Management Of Iccmentioning
confidence: 99%
“…In the setting of metastatic intrahepatic cholangiocarcinoma, a cohort study used the National Cancer Database showed that liverdirected local therapy was associated with improved survival. 24 Hu et al 22 evaluated prognostic factors, treatments, and survival outcomes of 81 patients with HCCPM. They found that liver resection might be associated with better survival when compared with ablation or transarterial chemoembolization in selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The CCA median survival is about 12 months. The prognosis is unfavorable in CCA because of the lack of response to chemotherapy and radiotherapy [ 14 , 15 ]. The only option that remains is palliative care, symptomatic therapy – pain management – in order to improve the patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%